Dopa decarboxylase gene polymorphisms and attention deficit hyperactivity disorder (ADHD): no evidence for association in the Irish population - GILL, MICHAEL; MCCARRON, MARY; HAWI, ZIARIH; FITZGERALD, MICHAEL (My University, 2001)
Dopa decarboxylase (DDC) is an enzyme which catalyses the decarboxylation of both dopa to dopamine and L-5 hydroxytryptophan to serotonin. Both catecholamines are major neurotransmitters of the mammalian nervous system. It has been suggested that genes involved in the dopaminergic system play a primary role in predisposing to attention deficit hyperactivity disorder (ADHD). In this study, the 4-bp insertion/deletion variant mapped to the first neuronally expressed exon 1 at the dopa decarboxylase gene and two microsatellite markers flanking the gene were investigated for possible association with ADHD. Using HHRR, we observed an increased transmission (though not significant) of the 4-bp insertion (allele 1) to ADHD cases (chi2 = 2.72, P = 0.1, RR = 1.25). However marginally significant excess transmission of allele 10 (213 bp) of the 3' microsatellite D7S2422 (~0.75 cM distal to dopa decarboxylase gene) was found (chi2 = 4.2, P = 0.04, RR=1.48). Interestingly, a haplotype containing both alleles is transmitted more frequently (chi2= 5, P = 0.025). Analysing data by the sex of transmitting parent showed a greater relative risk for paternal transmission of the 4-bp insertion allele and allele 10 of the D7S2422 (RR = 1.48 and 1.63 respectively). This provides preliminary evidence that this locus or a closely mapped DNA variant may be involved in the genetic susceptibility to ADHD. However, further studies are required to either confirm or refute these observations.
PUBLISHED
(264) PMID: 11443526 ABSTRACT:Dopa decarboxylase (DDC) is an enzyme which catalyses the decarboxylation of both dopa to dopamine and L-5 hydroxytryptophan to serotonin. Both catecholamines are major neurotransmitters of the mammalian nervous system. It has been suggested that genes involved in the dopaminergic system play a primary role in predisposing to attention deficit hyperactivity disorder (ADHD). In this study, the 4-bp insertion/deletion variant mapped to the first neuronally expressed exon 1 at the dopa decarboxylase gene and two microsatellite markers flanking the gene were investigated for possible association with ADHD. Using HHRR, we observed an increased transmission (though not significant) of the 4-bp insertion (allele 1) to ADHD cases (chi(2) = 2.72, P = 0.1, RR = 1.25). However marginally significant excess transmission of allele 10 (213 bp) of the 3' microsatellite D7S2422 ( approximately 0.75 cM distal to dopa decarboxylase gene) was found (chi(2) = 4.2, P = 0.04, RR=1.48). Interestingly, a haplotype containing both alleles is transmitted more frequently (chi(2)= 5, P = 0.025). Analysing data by the sex of transmitting parent showed a greater relative risk for paternal transmission of the 4-bp insertion allele and allele 10 of the D7S2422 (RR = 1.48 and 1.63 respectively). This provides preliminary evidence that this locus or a closely mapped DNA variant may be involved in the genetic susceptibility to ADHD. However, further studies are required to either confirm or refute these observations.
Keywords: attention deficit hyperactivity disorder (ADHD); dopamine; dopa decarboxylase; association; haplotype based haplotype relative risk (HHRR); Neuroscience; ADD/ADHD; ADD/ADHD; ADHD; ADHD; ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD); Adolescent Psychiatry; Attention Deficit Hyperactivity Disorder (ADHD); CHILD PSYCHIATRY; COMMUNITY PSYCHIATRY; CONSULTATION LIAISON PSYCHIATRY; CONSULTATION-LIAISON PSYCHIATRY; DISORDER ADHD; DOPA DECARBOXYLASE; Dopa decarboxylase gene polymorphisms; GENE POLYMORPHISM; GENE POLYMORPHISMS; GENERAL HOSPITAL PSYCHIATRY; LIAISON PSYCHIATRY; Neuropsychiatry; Neuropsychiatry; PSYCHIATRY; Psychiatry; Psychiatry; TRAINEES IN PSYCHIATRY; child and adolescent Psychiatry; neurodevelopmental psychiatry